Detection of KIT D816V in peripheral blood of children with manifestations of cutaneous mastocytosis suggests systemic disease. (28th November 2018) - Carter, Melody C.; Bai, Yun; Ruiz‐Esteves, Karina N.; Scott, Linda M.; Cantave, Daly; Bolan, Hyejeong; Eisch, Robin; Sun, Xiaoping; Hahn, Jamie; Maric, Irina; Metcalfe, Dean D.
Summary: The use of allele‐specific quantitative polymerase chain reaction to identify KIT D816V in the peripheral blood of adults with mastocytosis has been reported to have value in the diagnosis, assessment of disease burden and management of this disease. To examine the value of this assay in children with cutaneous manifestations of mastocytosis, we assessed data on 65 patients with all variants of paediatric‐onset mastocytosis, including those known to have systemic disease, to correlate KIT mutation status with clinical findings, serum tryptase levels and bone marrow histopathology. We found that KIT D816V was not identified in the peripheral blood of children known to have only cutaneous disease (specificity 100%) but was found in those known to have both cutaneous and systemic/probable systemic disease (sensitivity of 85·2%). These findings were the basis of the development of an algorithm to assist in the decision for when to perform a bone marrow biopsy in children presenting with cutaneous manifestations of mastocytosis.